Experimental study on the bond behavior of GFRP plate-high-strength concrete composite interfaces under the coupled effects of sustained load and seawater immersion. (April 2021) - Zhang, Pu; Hu, Yi; Pang, Yuyang; Zhang, Shuangquan; Zia, Asad; Gao, Danying; Zhu, Hong; Ahmed Sheikh, Shamim
Abstract: This paper presents an experimental study on the bond behavior between glass fiber-reinforced polymer (GFRP) plate and high-strength concrete under the coupled effects of sustained load and artificial seawater (60 °C constant temperature and 5 times seawater concentration) immersion. A specially designed preloading system was used to apply the sustained load on the specimens, and a new type of U-shaped shear key was applied under the coupled effect. A total of 48 double-lap shear specimens were tested to investigate the effects of coupled-effect time and interface type. The main properties of the bonded joints were examined, including the failure modes, ultimate load and load-slip curve. The test results showed that (1) the bonding performance between high-strength concrete and epoxy resin was substantially affected by the artificial seawater immersion; (2) the ultimate load of the double-lap shear specimens with four types of interfaces was reduced significantly with increasing coupled-effect time; (3) the premature failure occurred for each dry bond (DB) interface specimen with coupled effects, and the DB interface was not recommended under the coupled effects; (4) the ultimate load of the shear key combined with wet bond (SK-WB) interface was significantly greater than that of the other three types of interface under different coupled-effect ages; (5) the DB interface was the worst and the SK-WB interface was the best under the coupled effects in terms of the interface stiffness.